ABOUT THE PROBLEMS AND PROSPECTS OF ENTREPRENEURSHIP AMONG YOUNG PEOPLE IN THE MODERN REALITIES OF THE CORONAVIRUS PANDEMIC - R. Ustaev; O. Boris (Вестник Северо-Кавказского федерального университета)
In the article modern aspects of the development of youth entrepreneurship during the coronavirus pandemic are considered. The key problems of youth entrepreneurship in the context of a pandemic are identified. Possible measures of state support for youth entrepreneurship are proposed. The emphasis is placed on the fact that today it is necessary to radically restructure the forms and methods of work of modern enterprises. The prospects for the restoration of youth entrepreneurship caused by the crisis and the natural cyclical development of the economy are noted.